Simulation-based low-dose, high-frequency plus mobile mentoring versus traditional group-based training approaches on day of birth care among maternal and newborn healthcare providers in Ebonyi and Kogi States, Nigeria; a randomized controlled trial - Ugwa, Emmanuel; Otolorin, Emmanuel; Kabue, Mark; Ishola, Gbenga; Evans, Cherrie; Oniyire, Adetiloye; Olisaekee, Gladys; Onwe, Boniface; LeFevre, Amnesty E; Bluestone, Julia; Orji, Bright; Yenokyan, Gayane; et al. (BMC health services research, 2018)
Background There is limited information from low and middle-income countries on learning outcomes, provider satisfaction and cost-effectiveness on the day of birth care among maternal and newborn health workers trained using onsite simulation-based low-dose high frequency (LDHF) plus mentoring approach compared to the commonly employed offsite traditional group-based training (TRAD). The LDHF approach uses in-service learning updates to deliver information based on local needs during short, structured, onsite, interactive learning activities that involve the entire team and are spaced over time to optimize learning. The aim of this study will be to compare the effectiveness and cost of LDHF versus TRAD approaches in improving knowledge and skill in maternal and newborn care and to determine trainees’ satisfaction with the approaches in Ebonyi and Kogi states, Nigeria. Methods This will be a prospective cluster randomized control trial. Sixty health facilities will be randomly assigned for day of birth care health providers training through either LDHF plus mobile mentoring (intervention arm) or TRAD (control arm). There will be 150 trainees in each arm. Multiple choices questionnaires (MCQs), objective structured clinical examinations (OSCEs), cost and satisfaction surveys will be administered before and after the trainings. Quantitative data collection will be done at months 0 (baseline), 3 and 12. Qualitative data will also be collected at 12-month from the LDHF arm only. Descriptive and inferential statistics will be used as appropriate. Composite scores will be computed for selected variables to determine areas where service providers have good skills as against areas where their skills are poor and to compare skills and knowledge outcomes between the two groups at 0.05 level of statistical significance. Discussion There is some evidence that LDHF, simulation and practice-based training approach plus mobile mentoring results in improved skills and health outcomes and is cost-effective. By comparing intervention and control arms the authors hope to replicate similar results, evaluate the approach in Nigeria and provide evidence to Ministry of Health on how and which training approach, frequency and setting will result in the greatest return on investment. Trial registration The trial was retrospectively registered on 24th August, 2017 at ClinicalTrials.Gov: NCT03269240 .